Correlation of on Admission Levels of Serum Uric Acid with Acute Myocardial Infarction: Case: Control Study - Hayder Abdul-Amir Maki Al-Hindi (Journal of Global Pharma Technology, 2016)
Background: There are insufficient researchers studied serum uric acid (SUA) concentrations in patients with acute myocardial infarction (AMI or MI) at time of admission. We undertook the contemporary work to evaluate the value of SUA levels in admitted AMI subjects. Materials and methods: The study subjects consist of 260 people divided in two groups, 100 age and sex matched healthy controls with 160 patients with AMI (28-80 years) diagnosed by clinical, laboratory findings, and echocardiography. Study populations were stratified according to their levels of SUA at their first 6-12 hours of admission, into three tertiles: first (<5 mg/dl), second (5-6 mg/dl) and the third (>6.3 mg/dl). The concentrations of the three serum UA tertiles were studied for their association with AMI patients. Research biochemical evaluations were directed using conventional techniques. An accepted level of significance was P < 0.05. Results: For all study subjects, the mean age was 50.5±13.5 years. The ratio of men to women was 3.5:1 and there were no statistically substantial variations amongst the groups as regards the age and gender. The higher tertiles where positively correlated with increasing ages of individuals. The most common risk factors for all subjects of the study were hypertension (56%), then smoking (55%), then diabetes mellitus (26%). The mean serum concentrations of UA were higher significantly in those with AMI (5.96 ±1.8) than in control group (4.39 ± 1.3 mg/dl; P=0.05). Those with AMI has higher odds ratio (6.3, 95% CI: 2.26-17.6) than control group for the presence of highest Vis lowest SUA tertiles. Once several confounders (age, sex, diabetes mellitus, and hypertension) are being adjusted, the hazard ratios for developing AMI continue to be significant in the second and third tertiles of SUA. Conclusion: The outcomes of the study displayed that higher SUA concentrations are correlated with the incidence of AMI in admitted patients. High SUA levels independently can be considered as unconventional risk factor for the incidence of AMI. Key words: Acute myocardial infarction, Uric acid and hyperuricemia.